2011
DOI: 10.7748/ns2011.02.25.24.49.c8344
|View full text |Cite
|
Sign up to set email alerts
|

Long-term urethral catheterization

Abstract: This article discusses long-term urethral catheterisation, focusing on the relevant anatomy and physiology, indications for the procedure, catheter selection and catheter care. It is important that nurses have a good working knowledge of long-term catheterisation as the need for this intervention will increase with the rise in chronic health conditions and the ageing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Also, the present study results revealed that there was statistically significant difference between checking securing of urinary drainage system and results of urine culture. This finding is supported by Turner and Dickens (2011) (42) who found that it is vital to fix the drainage device securely to prevent, discomfort and infection.…”
Section: Resultsmentioning
confidence: 64%
“…Also, the present study results revealed that there was statistically significant difference between checking securing of urinary drainage system and results of urine culture. This finding is supported by Turner and Dickens (2011) (42) who found that it is vital to fix the drainage device securely to prevent, discomfort and infection.…”
Section: Resultsmentioning
confidence: 64%